Bapera : ritual, corpo e imagem por uma etnografia da estética ameríndia na enciclopédia bororo - Rodrigues, Danilo Gonçalves (2024)
This ethnographic research aims to conduct an analysis of the “partial connections” present in the Salesian imagery production and its potential contribution to the understanding of ethnographic relationships between different cosmologies, especially between Christian cosmology and that of the Boe Bororo. This approach is not without tensions and conflicts, as it involves different subject and body positions, as emphasized by Haraway. A connection is established between this analysis and Alfred Gell's proposition, speculating on how images, paintings, and ornaments constitute a “relational nexus” between beings, people, and the bodies. The research is conducted through an approach that integrates anthropology of the archive and art, with the Bororo Encyclopedia being understood as an object of study and problematization.